Inappropriate Total Oxidant/Antioxidant Status, Nitric Oxide Oxidation End Products and Trace Element Levels in Patients with Inflammatory Bowel Disease - Erfan Mohammadi (Shiraz University of Medical Sciences, 2018)
Background: This study aimed at evaluating oxidant and antioxidant markers (including nitrite, nitrate, total antioxidant capacity(TAC), malondialdehyde (MDA), iron, selenium, glutathione peroxidase (GPx), and glutathione reductase (GR) in patients withinflammatory bowel disease (IBD) and compare them with healthy controls.Methods: Serum samples were obtained from 35 patients (19 ulcerative colitis (UC) and 16 Crohn’s disease (CD) in the active phaseof the disease) and 30 healthy controls. Serum levels of nitrite and nitrate, TAC, MDA, iron, selenium, glutathione peroxidase, andglutathione reductase were measured. The results were compared between the two groups using independent t-student test. ThePearson’s correlation coefficient (for continuous data) was performed using the SPSS software.Results: Serum levels of nitrite, nitrate, and MDA were significantly higher (P = 0.001) in patients with IBD, while the levels of TAC,trace elements, glutathione peroxidase (GPx), and Glutathione Reductase (GR) levels were lower (P < 0.05) in patients with IBD.However, when females were considered separately, Gpx and GR activities were not significantly different in those with and withoutIBD. The present results showed that nitrite, MDA, GPx, GR, and Se: MDA ratio had the strongest correlation with disease activityscore.Conclusions: There is an imbalance between oxidant and antioxidant properties in patients with IBD, which highlights the role ofoxidative stress in the pathogenesis of this disease.